Implementation of Tutoring Services through Ratu Santa's Strategy in English Vocabulary Mastery for Deaf Students - Kartika Hajati; Muhammad Aswad; Masrwati Masrawati (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to analyze the implementation of tutoring with the Ratu Santa strategy as one of the guidance and counseling services by English teachers to encourage the optimization of student learning in vocabulary mastery. This study uses a qualitative method. The subjects of this research were an English teacher and 5 grade VIII students. Obtaining data is done through observation, interviews and documentation. Data analysis uses data condensation, data display, and conclusion drawing verifying. This study concludes first, there are four strategies used by English teachers in teaching vocabulary to deaf students, namely: sign language, body language (gestures), written language, and tadoma (Ratu Santa). And second, the teacher implemented the strategies by combining all of them. The teacher showed the material such as explanation and vocabularies to students by wrote it on the whiteboard. Next, the teacher explains the material to the students by using sign language also gesture, when the students could not read lips language the teacher taught using tadoma strategy.